A basic inequality for submanifolds in a cosymplectic space form. (9th February 2003) - Kim, Jeong-Sik; Choi, Jaedong
Abstract : For submanifolds tangent to the structure vector field in cosymplectic space forms, we establish a basic inequality between the main intrinsic invariants of the submanifold, namely, its sectional curvature and scalar curvature on one side; and its main extrinsic invariant, namely, squared mean curvature on the other side. Some applications, including inequalities between the intrinsic invariantδ M and the squared mean curvature, are given. The equality cases are also discussed.